Understandings about graphs by field school teachers - Souza, Josilane de; Monteiro, Carlos Eduardo Ferreira (Universidade Estadual de Campinas, 2020)
Interpretation of statistical data presented in graphs is associated with competences that must be developed by citizens during their schooling. In Brazil, the Field Education contexts are challenging since it demands the consideration of contextual specificities. This article discusses aspects of a research that investigated comprehension about graphs that of field school teachers. The research data came from interviews and workshops on statistical literacy. The results obtained from the interviews suggested some gaps in relation to the concepts of Field Education, as well as evidenced difficulties regarding the interpretation of graphs. The workshops seemed to be important education venues for statistical literacy, as teachers were encouraged to enrich their pedagogical practice.